A TWO-DIMENSION TIME-DOMAIN-THRESHOLD METHOD FOR LOAD SPECTRA EDITING AND ITS APPLICATION - YU JiaWei; MA JianJun; ZHENG SongLin; QIAN ChunLei (Jixie qiangdu)
In order to avoid dependence of structural local detailed strain/stress spectrum of the traditional Time Correlated Fatigue Damage Editing method, a Spectra Two-dimension Time-domain-threshold Editing（STTE） method was proposed for the problem of spectrum compilation of vehicle road-load-simulation testing. Taking vehicle road-load-simulation testing as an example, the testing target spectrum was developed by applying the STTE method combined with the pseudo damage retention principle. Theoretical analyses and test bench results showed that the developed accelerated spectra not only shorten test time effectively, but also well retain characteristics of the original load spectra. Additionally, the accelerated spectra well realized spectrum simulation and durability evaluation effect under the test bench condition. The proposed STTE method can provide reference for load spectrum editing of vehicle road-load-simulation testing.